Eliminating Institutional Barriers to Career Advancement for Diverse Faculty in Academic Surgery. Issue 1 (July 2019) - Newman, Erika A.; Waljee, Jennifer; Dimick, Justin B.; Mulholland, Michael W.
Abstract : N/A: There is critical need to address achievement barriers in Academic Medicine. Although opportunities for professional development of women and underrepresented minority physician scientists are growing, academic promotion rates remain historically low. Moreover, underrepresented groups are not likely to advance to decanal and leadership positions. To eliminate institutional barriers to achievement for diverse faculty, strategies to strengthen environment, recruitment, professional development, and leadership were implemented. This multifaceted approach is adaptable to Academic Surgery universally and we wish to share early progress.